The influence of costs accounting and professional accountant on the training of sales price of micro and small enterprises in Porto Velho city - Licório, César (2018)
The aim of this paper is to identify the contribution of cost accounting and professional accountant, as a competitive advantage in the formation of the selling price of micro and small enterprises in Porto Velho city. The methodology used for the preparation of this work was a survey, of course, literature, descriptive and qualitative, as well as a field study using questionnaire. Starting from the following problem: in a globalized economy, with such aggressive pricing, which the importance of cost accounting and the advice of a professional accountant in the formation of the selling price? This research is justified in the increasingly competitive market, such as the Old Port, where any detail can bring a great advantage in the bottom line. The main results identified show that the vast majority of micro and small entrepreneurs of Porto Velho do not use cost accounting, nor the aid of a counter, a qualified professional with the necessary techniques to support the formation of their prices so they do not incur errors that bring you losses also do not use the advantage of the information that the cost accounting features for decision making. In a globalized economy, specifically in a growing market as the Porto Velho any detail can make the difference between success and failure of a micro and small business, cost accounting becomes an increasingly necessary tool, and it is undeniable the contribution that the counter as specialized professional can bring to the manager has grounds to form their prices, deciding marketing strategies, and control costs.